Krajské zřízení - Sůrová, Petra (Univerzita Pardubice, 2006)
Bakalářská práce se zabývá krajským zřízením: historickým vývojem krajského zřízení v České republice,decentralizací veřejné správy a aplikací zákona č. 129/2000 Sb., o krajích v České republice a Pardubickém kraji.

The bachelor work is interested in the regional constitution: the historical development of the regional constitution in the Czech republic, the decentralization of the public administration and implementation of the code No 129/2000 Collection of Laws, about regions in Czech republic and in the Pardubice region
Regional constitution
Keywords: regional constitution; regions; Pardubice Region; krajské zřízení; kraje; Pardubický kraj; reformy